A qualitative exploration of psychosocial specialists' experiences of providing support in UK burn care services - Ella Guest; Catrin Griffiths; Diana Harcourt (SAGE Publishing, 2018)
Introduction: A burn can have a significant and long-lasting psychosocial impact on a patient and their family. The National Burn Care Standards (2013) recommend psychosocial support should be available in all UK burn services; however, little is known about how it is provided. The current study aimed to explore experiences of psychosocial specialists working in UK burn care, with a focus on the challenges they experience in their role. Methods: Semi-structured telephone interviews with eight psychosocial specialists (two psychotherapists and six clinical psychologists) who worked within UK burn care explored their experiences of providing support to patients and their families. Results and Discussion: Thematic analysis revealed two main themes: burn service-related experiences and challenges reflected health professionals having little time and resources to support all patients; reduced patient attendance due to them living large distances from service; psychosocial appointments being prioritised below wound-related treatments; and difficulties detecting patient needs with current outcome measures. Therapy-related experiences and challenges outlined the sociocultural and familial factors affecting engagement with support, difficulties treating patients with pre-existing mental health conditions within the burn service and individual differences in the stage at which patients are amenable to support. Conclusion: Findings provide an insight into the experiences of psychosocial specialists working in UK burn care and suggest a number of ways in which psychosocial provision in the NHS burn service could be developed.